PENGUATAN KOMPETENSI GURU MELALUI PELATIHAN DESAIN PEMBELAJARAN BERBASIS GAMMA: PRESENTATIONS AND SLIDE DECKS WITH AI DI SEKOLAH DASAR - Rizal, A; SAS, Abdillah; Burhan, Burhan; Jainuddin, Jainuddin; Arwien, Rizki Trisnawaty; Sahib, Nurfaizah; Safira, Ifa; Irwandi, Andi; Gerianus, Gerianus (DEVOSI, 2025)
The training on Gamma-based instructional design aims to enhance teachers' ability to create effective presentations and slide decks using artificial intelligence (AI). The training methods include delivering material on the use of Gamma Presentations and Slide Decks with AI, interactive discussions, and hands-on practice, where participants are guided in developing engaging and comprehensible instructional content. This training incorporates design software and AI applications to improve the quality and attractiveness of teaching materials. The community service initiative targets teachers at UPT SPF SDN 1 Mongisidi, a leading elementary school in Makassar City. Through group assignments, teachers are also given opportunities to collaborate, exchange ideas, and provide feedback to one another. Evaluation results indicate a significant improvement in teachers' understanding of instructional design, as well as increased confidence in utilizing technology. This training is expected to have a positive impact on the quality of elementary education, encourage innovation in teaching, and foster a more interactive learning environment.